2018
DOI: 10.1093/jjco/hyy045
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of heparinoid moisturizer as a prophylactic agent for radiation dermatitis following radiotherapy after breast-conserving surgery: a randomized controlled trial

Abstract: Preventive application of heparinoid moisturizer from the first day of WBRT significantly increased water content and helped to improve skin desquamation and dryness compared with no treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 31 publications
0
27
0
2
Order By: Relevance
“…The stratum corneum functions as a barrier that prevents water loss and protects the body from external stressors [ 21 ]. Ionizing radiation impairs the skin barrier functions of the stratum corneum, resulting in increased transepidermal water loss and decreased water content [ 22 ]. Consistent with our findings, previous investigations have shown that the water content in irradiated skin continuously decreases as radiotherapy sessions proceed over time.…”
Section: Discussionmentioning
confidence: 99%
“…The stratum corneum functions as a barrier that prevents water loss and protects the body from external stressors [ 21 ]. Ionizing radiation impairs the skin barrier functions of the stratum corneum, resulting in increased transepidermal water loss and decreased water content [ 22 ]. Consistent with our findings, previous investigations have shown that the water content in irradiated skin continuously decreases as radiotherapy sessions proceed over time.…”
Section: Discussionmentioning
confidence: 99%
“…[2527] In our previous report, heparinoid moisturizer maintained stratum corneum WC and reduced skin desquamation and dryness. [14, 15] The skin itself is not the primary target of RT in breast-conserving therapy. [27] However, the skin exposure to significant doses is inevitable during RT, thereby causing damage to the sweat and sebaceous glands.…”
Section: Discussionmentioning
confidence: 99%
“…The primary endpoint of the WC of stratum corneum and the other secondary outcomes of signs and symptoms associated with acute radiation dermatitis were previously reported. [14, 15] In this article, we report the time-course of sebum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Os sintomas podem aparecer durante ou mesmo após o término do tratamento podendo variar de um leve eritema (radiodermite grau I) até exulcerações importantes (radiodermite grau IV) que levam a interrupção do tratamento e incapacidades e limitações nos pacientes afetados. 4 O diagnóstico e tratamento adequado dessas complicações são extremamente importantes para que não haja uma diminuição das doses dos medicamentos e até mesmo interrupção do tratamento oncológico proposto que podem impactar de forma negativa nos resultados do tratamento e taxas de sobrevida dos pacientes. 5 Tendo em vista que o intuito principal dos produtos para cuidados da pele é promover um suporte exógeno para manter a barreira cutânea intacta, assim como preservar a hidratação da pele visando reduzir e aliviar os sintomas de xerose e consequentemente, prurido, infeções secundárias e reações de sensibilização, além de tornar a pele mais resistente aos efeitos da radiação, o objetivo do presente trabalho foi verificar a aceitabilidade cutânea em peles oncológicas dos produtos: Klaviê Creme, Klaviê Loção e Klaviê Sabonete Líquido por meio de observação da melhora na hidratação e redução da perda transepidérmica de água da pele em pacientes em tratamento oncológico (quimioterapia ou radioterapia).…”
Section: Introductionunclassified